RACIONALIDADE POLÍTICA E EDUCAÇÃO: A (Re) invenção do Ensino Médio brasileiro em reformas (2017-2022) - Marcelo Correa Pires (2024)
This research discusses the effects and practices resulting from the High School Reform, sanctioned through Executive Order No. 746 on September 22, 2016, which later became Law No. 13,415 on February 16, 2017. The objective is to show that this reform brought various impacts on the formal education of Brazilian youth, considering the neoliberal principles that characterize the context of Governmentality, a concept coined by Michel Foucault (1926-1984), which describes how institutions, knowledge, and strategies have been used to govern individuals since the 18th century. The methodological orientation encompasses the study of a complex set of institutions, procedures, analyses, reflections, calculations, and tactics employed to exercise a specific type of power concentrated on the population. This helps to understand how the High School Reform is part of a movement of labor, pension, tax, political, and fiscal reforms triggered in the country since 2016 during the government of Michel Temer, directing budget cuts and freezing public spending, mainly in the discourse on the guarantees of social and educational policy protection. To frame the analysis and understand that Neoliberalism corresponds to the local culture, the effects of this rationale of government were analyzed, as they produced an immediate alignment of the State Education Network of Mato Grosso do Sul (REE/MS). Law No. 4,973, dated December 29, 2016, implemented the Full-Time Education program, called Schools of Authorship. The results indicate a condition of continued war by other means, which demands from education the solution to correct social distortions accumulated throughout history at this level of training. They reveal a set of goals and strategies in the educational field that often act to regulate individuals in their specificities. This leads them to become entrepreneurs of themselves through the development of technologies and efforts that seek to enable them to acquire minimum skills and competencies to recognize themselves as subjects in a society that advocates protagonism through different economic, social, and cultural relations. This approach lacks an effective intention of transformation, maintaining conservative practices that underpin the country, neglecting educational and social rights, putting at risk and compromising the exercise of citizenship and the very sense of the democratic process, which often circulates through authoritarianism.